Investigation of early magnetic field and angular momentum in ultrarelativistic heavy-ion collisions via D*+ spin alignment with ALICE - Sharma Himanshu (EPJ Web of Conferences)
Heavy quarks, i.e. charm and beauty, are produced at the initial stages of heavy-ion collisions, on a time scale shorter than the medium formation time, and are sensitive to the initial angular momentum of the system and the magnetic field produced perpendicular to the reaction plane (defined by the impact parameter direction and beam direction) in non-central heavy-ion collisions. In the presence of a large angular momentum and initial magnetic field, the charm quark can be polarized. Experimentally, the heavy-flavor polarization can be probed by measuring the spin density matrix element (ρ00) of spin-1 mesons such as D*+ mesons. Any deviation of the parameter from 1/3 can be attributed to the spin alignment of the D∗+ meson. In these proceedings, we present the first measurement of the ρ00 parameter of prompt D*+ mesons in Pb–Pb collisions at √sNN = 5.02 TeV, exploiting the data sample collected by the ALICE Collaboration during LHC Run 2. A comparison with the J/ψ polarization measurement is also reported to investigate the effect of the magnetic field. Moreover, the ρ00 parameter of D*+ mesons measured in pp collisions is also presented.